PENGGUNAAN ALGORITMA K – MEANS CLUSTERING UNTUK MENENTUKAN PENILAIAN KEDISIPLINAN KARYAWAN RUMAH SAKIT ROYAL PRIMA - Winda Nia Purba; Michael Kosasih; Donny Kallamas; Michael Wijaya (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2023)
Hospital is a place that has community service facilities engaged in the health sector, in the hospital provides outpatient and inpatient care. A hospital has several services such as health services for the elderly, health services for children and health services for adults. Before a hospital implements all these services for the community, all employees of the hospital need to do a training process so that the management of the hospital can assess the level of discipline of all employees of the hospital. Apart from the training process, the department of a hospital company will conduct an employee assessment, which the goal is to find out the level of discipline of the hospital employees. The research methodology used in this study is descriptive. a research method used to discuss a problem by researching, processing data, analyzing and describing with regular discussion. In this descriptive method research, the author uses three aspects that are the criteria for discipline of Royal Prima Hospital Employees, namely Discipline, Absence and Appreciation. The data collected by the author is through observation techniques and sampling techniques.